Inguinal Hernia: Diagnosis and Management - Nabila Aisyah Putri; Nur Feby Febiana Agistany; Raditya Bayu Farizil Akhyar; Salsabila Chauna; Wardha Novia Annisa; Zikrul Haikal (Jurnal Biologi Tropis, 2023)
The inguinal hernia is the subcutaneous part of the peritoneum containing the abdominal viscera that exits through the inguinal canal or directly through the abdominal wall. Most patients do not realize they have an inguinal hernia until swelling arises in the thigh fold area or pain in the groin area. The purpose of this literature review is to provide an update regarding the diagnosis and management of inguinal hernias. The diagnosis of an inguinal hernia is largely based on the history and physical examination, whereas imaging is rarely performed unless there is a certain suspicion. Surgical management can be performed on patients with symptoms, while asymptomatic patients can be subjected to conservative therapy.